Group Action Without Group Minds. (27th February 2021) - Silver, Kenneth
Abstract: Groups behave in a variety of ways. To show that this behavior amounts to action, it would be best to fit it into a general account of action. However, nearly every account from the philosophy of action requires the agent to have mental states such as beliefs, desires, and intentions. Unfortunately, theorists are divided over whether groups can instantiate these states—typically depending on whether or not they are willing to accept functionalism about the mind. But we can avoid this debate. I show how a more general view of action captures what is central to action without mentioning mental states, and I argue that a group's members can fulfill the role in group action that mental states play in our actions. Group behavior is explicable in terms of reasons, regardless of whether the group itself cognizes those reasons. After discussing the kind of reasons at issue and arguing that groups can act in light of them without minds, I assess how this account bears on the question of group responsibility.